The church in a world of religions: working papers in theology - Greggs, Tom (T&T Clark, 2021)
"In this collection of essays, Tom Greggs explores the nature of the church in a world of many religions. Greggs' writings on the Church and on other religions emphasize the importance of attentiveness to Christ and the Holy Spirit, and both are simultaneously generous and particularist. The first part of the book addresses the Church as it is brought into being by the Spirit in glorifying God, celebrates the sacraments, respects the authority of the creeds, is generously Catholic, and critiques its own religion. The second part looks at the church in a pluralist context as it engages in inter-faith dialogue, expresses both particularism and universalism, speaks of Christ with many names, and reads scripture and understands the many covenants found there. Greggs offers a programmatic conclusion, setting an agenda for theologies of the church and of other religions and their simultaneous relationality"--